Peran Penyuluh Pertanian Terhadap Kelompok Tani Victory Di Desa Kakaskasen Tiga Kecamatan Tomohon Utara Kota Tomohon - Pandia, Desmiranda; Manginsela, Elsje Pauline; Tangkere, Ellen Grace (AGRI-SOSIOEKONOMI, 2023)
The purpose of this study was to analyze the role of extension workers in providing agricultural extension to the Victory Farmers Group. The research was carried out for 3 (three) months, starting from January to March 2023 in Kakaskasen Tiga Village, North Tomohon District, starting with preparation, data collection to the preparation of research reports. The data in the study are primary and secondary data. Primary data is a source of data obtained directly from the field by interviewing members of the Victory farmer group. Secondary data is data obtained from other sources, for example government agencies such as village halls. Sampling using the census method, the population that is the object of research is all members of the Victory Farmer Group including the management of both the chairman, secretary and treasurer in Kakaskasen 3 Village. The number of samples is all members of the farmer group, namely 10 people. The results showed that the average score of the role of extension agents with 3 elements was in the medium category, motivators, facilitators, and communicators and there was 1 element in the high category, namely educators, which showed that the assessment of farmer group members on the role of agricultural extension agents had an average score as a motivator of 2.25 which was in the medium category, the average score as a facilitator of 2.27 which was in the medium category, the average score as an educator of 2.53 which was in the high category, the average score as a communicator of 2.23 which was in the medium category.